The use of corn and buckwheat flour in the production of bakery products - E. N. Efremova; A. I. Belyaev; N. Y. Petrov; E. A. Zenina (Новые технологии, 2024)
Currently, to make profit all entrepreneurs expand the range of products. The purpose of the research is introduction and use of a combination of different types of flour in bread baking in order to expand the range of bakery products of improved quality. The objectives of the research are to study the organoleptic quality indicators of the experimental sample; to conduct a study on physical and chemical quality indicators of the experimental sample; to determine the economic feasibility of using a new recipe in bread production. The research was carried out on the basis of the Department of Processing Technologies and Food Security of Volgograd State Agrarian University. To expand the range of bakery products, 40% of corn flour and 10% of buckwheat flour were used to replace 50% of wheat flour. The bread was baked using the non-steam method. When conducting an organoleptic assessment of bread, the experimental sample complied with the requirements of GOST 27669-88 «Wheat baking flour. Method of trial laboratory bread baking.» The taste became sweeter, the porosity became fine and thin-walled, and the color of the crumb became light brown. According to physicochemical indicators, the experimental sample was 56 g larger in bread volume, and the crumb moisture content was 43%. The economic efficiency of bread production was calculated. The profitability of experimental bread production was 44%, which was 14% higher than the control (wheat) sample.  I t is recommended to produce bread using a combination of three types of flour, to increase the output at enterprises. This type of bread, in terms of organoleptic and physico-chemical indicators, has proven itself to be a more advantageous example of a bakery product compared with wheat bread.